Characterization of microbial biofilms on marine plastics: community development and density implications for vertical transport dynamics - Joern, Gregory M.; Pedrosa-Pàmies, Rut; Jiang, Xiangtao; Liu, Zhanfei; Bochdansky, Alexander B. (Frontiers in Marine Science, 2025)
Marine plastic pollution poses a significant and escalating threat to ocean ecosystems, with microbial colonization on plastics playing a critical role in determining their environmental fate. Despite the recognized importance of microbial biofilms, their composition, dynamics, and functional contributions on buoyant plastics remain poorly understood. In this study, we leveraged a novel integrative approach by simultaneously employing 16S, 18S, and ITS sequencing alongside microscopy, lipidomics, pigment analysis, adenosine triphosphate and biogenic silica quantification. This comprehensive methodology allowed for a thorough characterization of microbial growth and community dynamics on plastic debris in a mid-latitude, tidal sub-estuary. Our analyses consistently identified diatoms, due to their silica shells, as the sole ballast-bearing microorganisms within the biofilm. By examining the accumulation of biogenic silica on plastic surfaces, we evaluated the potential role of microbial biofilms in influencing plastic sinking behavior in the water column. Our findings indicate that the production of microbial ballast material alone is insufficient to significantly alter the buoyancy of most buoyant plastics larger than 15 or 40 μm (depending on shape) under nutrient-rich, undisturbed conditions. These results suggest that additional processes, such as metazoan colonization or sediment accumulation, are likely necessary to transport larger buoyant plastics to deeper waters.